Nationwide survey of urological specialists regarding male infertility: results from a 2015 questionnaire in Japan. (4th October 2017) - Yumura, Yasushi; Tsujimura, Akira; Imamoto, Takashi; Umemoto, Yukihiro; Kobayashi, Hideyuki; Shiraishi, Koji; Shin, Takeshi; Taniguchi, Hisanori; Chiba, Koji; Miyagawa, Yasushi; Iwamoto, Teruaki
Abstract: Purpose: To investigate the incidence, etiology, treatment indications, and outcomes regarding infertile male patients in Japan. Methods: Between April, 2014 and March, 2015, the authors contacted 47 clinical specialists in male infertility who had been certified by the Japan Society for Reproductive Medicine. The participating clinicians were sent a questionnaire regarding information on their infertile patients, according to etiology and the number and success rates of male infertility operations that had been performed in their practice. Results: Thirty‐nine specialists returned the questionnaire and provided information regarding 7268 patients. The etiology of infertility included testicular factors, sexual disorders, and seminal tract obstruction. During the study year, the clinicians performed varicocelectomies, testicular sperm extractions (TESEs), and re‐anastomoses of the seminal tract. The rate of successful varicocelectomies was >70%. The sperm retrieval rates with conventional TESE and microdissection TESE were 98.3% and 34.0%, respectively, while the patency rates with vasovasostomy and epididymovasostomy were 81.8% and 61.0%, respectively. Conclusion: Surgical outcomes for infertile male patients are favorable and can be of great clinical benefit for infertile couples. To achieve this, urologists should work in collaboration with gynecological specialists in order to optimize the treatment of both partners. Abstract :